Yours cheerfully : a novel - Pearce, A. J. (Amanda-Jane) (The Emmy Lake chronicles, 2021)
"From the author of the "jaunty, heartbreaking winner" (People) and international bestseller Dear Mrs. Bird, a new charming and uplifting novel set in London during World War II about a plucky aspiring journalist. London, November 1941. Following the departure of the formidable Henrietta Bird from Woman's Friend magazine, things are looking up for Emmeline Lake as she takes on the challenge of becoming a young wartime advice columnist. Her relationship with boyfriend Charles (now stationed back in the UK) is blossoming, while Emmy's best friend Bunty, still reeling from the very worst of the Blitz, is bravely looking to the future. Together, the friends are determined to Make a Go of It. When the Ministry of Information calls on Britain's women's magazines to help recruit desperately needed female workers to the war effort, Emmy is thrilled to be asked to step up and help. But when she and Bunty meet a young woman who shows them the very real challenges that women war workers face, Emmy must tackle a life-changing dilemma between doing her duty and standing by her friends. Every bit as funny, heartwarming, and touching as Dear Mrs. Bird, Yours Cheerfully is a celebration of friendship-a testament to the strength of women and the importance of lifting each other up, even in the most challenging times"--